PRIVASI KOMUNIKASI: ANTARA BATAS PRIBADI DAN BATAS KOLEKTIF - Parapat, Nelson Halong (Istek Widuri Jakarta, 2019)
This paper provides us with an understanding of communication privacy, which is how we own and manage private information in interpersonal communication. Management of private information includes the setting of personal and collective boundaries, between which the two boundaries span the process of communication privacy regarding individual private information.Communication privacy is the management of the tension between the desire to be open or closed (privacy), between the need to remain personal or to be part of togetherness (collective). Individuals who are involved in a relationship with other individuals will continue to manage the boundary lines within themselves, namely between personal boundaries and collective boundaries, between feelings or thoughts that he wants to share and those he does not want to share with others. Communication privacy management are regulating the privacy of individual private information. Privacy always relates to the opening or disclosure of private information. Private information is information that is owned by an individual that is stored in his personal boundary whose disclosure potential is determined by intimacy factors.Personal boundaries in communication privacy are lines that limit when private information is kept by an individual and is not opened to other individuals. A collective boundary in communication privacy is an intersection of the personal privacy limits of the shared owners of personal information, all of whom are jointly responsible for that information. Boundary turbulence is a disruption of privacy management and relational trust that occurs when collective privacy boundaries are not synchronized. Limitation turbulence arises when boundary coordination rules are unclear or when people's expectations for privacy management conflict with one another.